Optimization Of The Program Of Environmentally Conscious Areas Of Population Administration (KALIMASADA) In Pakal District Surabaya City - Mahrani, Sindy; Hardjati, Susi (Universitas Airlangga, 2023)
Abstract Public services in Indonesia still face challenges, such as the increasing number of complaints. Moreover, East Java province has the most protests in Indonesia, and the city of Surabaya also has the highest number of complaints in East Java. One of the public services in the city of Surabaya is population administration services at the Surabaya City Population and Civil Registration Service. However, some still are unaware of the importance of population administration documents, so the government launched the Population Administration Aware Community Environmental Area (KALIMASADA) program. As in the Pakal sub-district, 416 people do not have orderly population administration. This research uses program optimization theory to analyze how to optimize the Population Administration Awareness Area (KALIMASADA) program in Pakal District. This research design is descriptive qualitative using primary data through interviews with key informants determined by purposive sampling, observation, and documentation-data”data analysis techniques using interactive models by Miles and Huberman. The results of this research are as follows: 1) The aim is to show that there is coordination between officers, Kasipem, and Head of RT in the KALIMASADA program so that time and costs can be minimized. 2) Alternative decisions show that the collaboration between officers and the RT Head ensures that the community can access services easily. However, there are still officers and the public who do not understand KALIMASADA. 3) Limited resources indicate that there are still obstacles in sub-district budget allocation and a lack of skills of officers in Pakal Sub-district. Still, the availability of infrastructure, such as the RW/RT Hall and internet access, is quite good. Keywords: Optimization, Population Administration, RW Hall Services, Pakal District Abstrak Pelayanan publik di Indonesia masih menghadapi tantangan seperti meningkatnya jumlah pengaduan. Terlebih lagi provinsi jawa timur memiliki pengaduan terbanyak di indonesia dan kota surabaya juga memiliki jumlah pengaduan terbanyak di jawa timur. Salah satu pelayanan publik di Kota Surabaya adalah pelayanan administrasi kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya. Namun, masih terdapat masyarakat yang kurang menyadari akan pentingnya dokumen adminsitrasi kependudukan sehingga pemerintah meluncurkan program Kawasan Lingkungan Masyarakat Sadar Administrasi Kependudukan (KALIMASADA). Seperti halnya di kecamatan pakal sebesar 416 jiwa yang belum tertib administrasi kependudukan. Penelitian ini bertujuan untuk menganalisis mengenai bagaimana optimalisasi program Kawasan Lingkungan Sadar Administrasi Kependudukan (KALIMASADA) di Kecamatan Pakal dengan menggunakan teori optimalisasi program. Desain penelitian ini adalah kualitatif deskriptif menggunakan data primer melalui wawancara dengan key informan yang ditentukan secara purposive sampling, observasi, dan dokumentasi. Teknik analisis data menggunakan model interaktif oleh miles and Huberman. Hasil penelitian ini adalah 1) Tujuan, menunjukkan bahwa adanya koordinasi antara petugas, Kasipem dan Ketua RT dalam program KALIMASADA sehingga dapat meminimalisir waktu dan biaya. 2) Alternatif keputusan, menunjukkan bahwa adanya kolaborasi petugas dan Ketua RT memastikan bahwa masyarakat dapat mengakses layanan dengan mudah. Namun masih terdapat petugas dan masyarakat yang belum paham terkait KALIMASADA. 3) Sumberdaya yang membatasi, menunjukkan bahwa masih terdapat kendala dalam alokasi anggaran kecamatan, kurangnya keterampilan petugas di Kecamatan Pakal, namun memiliki ketersediaan infrastruktur sudah cukup baik, seperti adanya Balai RW/RT dan akses internet. Kata kunci: Optimalisasi, Administrasi Kependudukan, Pelayanan Balai RW.